Do Access to Finance, Technical Know-How, and Financial Literacy Offer Women Empowerment Through Women’s Entrepreneurial Development? - Andriamahery, Anselme; Qamruzzaman, Md. (Frontiers in Psychology, 2022)
The motivation of the study is to gauge the effects of access to finance, technical know-how, and financial literacy on women's empowerment through establishing women's entrepreneurial sustainability. A sample of 950 women-owned SMEs was considered, and structured questionnaires were sent from getting target responses. After careful assessment through the data cleansing procedure, it was found that only 795 responses are suitable for further investigation, implying the sample response rate for the study is 74.71%. The study implemented structural equation modeling and multivariate regression analysis for gauging the causal association that is direct and indirect effects of target variables. According to findings, a positive statistically significant linkage was revealed with women's entrepreneurship sustainability and women empowerment. Furthermore, the mediating effects were also established for women's empowerment. According to the study findings, it is suggested that for women entrepreneurship sustainability, effective policies surrounding financing accessibility, technical knowledge expansion, and financial understating have to be promulgated in the economy, which allows bringing women empowerment at large.